PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS DAN UKURAN PERUSAHAN TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN WHOLESALE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zyotya Melviana Kusuma; Tiara Kusuma Dewi; I Ketut Yudana Adi (Universitas Triatma Mulya, 2022)
This research was conducted on a wholesale company in Indonesia. The purpose of this study was to determine the effect of profitability, liquidity, solvency and firm size on audit report lag in wholesale companies in Indonesia. The independent variables in this study are profitability (X1), liquidity (X2), solvency (X3) and firm size (X4). While the dependent variable in this study is the audit report lag. The population in this study are all wholesale companies listed on the Indonesia Stock Exchange in 2017-2020 with a total of 12 companies that meet the research criteria that have been set. The research method used is quantitative research with data analysis using multiple linear regression analysis which is processed with the SPSS 16 statistical program. The results of the analysis show the regression model Y = 55,734 -22.483X1-1,289X2-19,903X3+1,335X4+e. The results of this study indicate that audit report lag is significantly affected by solvency and firm size. Liquidity and profitability do not affect audit report lag.